Four-Dimensional Printing Hierarchy Scaffolds with Highly Biocompatible Smart Polymers for Tissue Engineering Applications - Miao, Shida (Tissue Eng Part C Methods, 2016)
The objective of this study was to four-dimensional (4D) print novel biomimetic gradient tissue scaffolds with highly biocompatible naturally derived smart polymers. The term “4D printing” refers to the inherent smart shape transformation of fabricated constructs when implanted minimally invasively for seamless and dynamic integration. For this purpose, a series of novel shape memory polymers with excellent biocompatibility and tunable shape changing effects were synthesized and cured in the presence of three-dimensional printed sacrificial molds, which were subsequently dissolved to create controllable and graded porosity within the scaffold. Surface morphology, thermal, mechanical, and biocompatible properties as well as shape memory effects of the synthesized smart polymers and resultant porous scaffolds were characterized. Fourier transform infrared spectroscopy and gel content analysis confirmed the formation of chemical crosslinking by reacting polycaprolactone triol and castor oil with multi-isocyanate groups. Differential scanning calorimetry revealed an adjustable glass transition temperature in a range from −8°C to 35°C. Uniaxial compression testing indicated that the obtained polymers, possessing a highly crosslinked interpenetrating polymeric networks, have similar compressive modulus to polycaprolactone. Shape memory tests revealed that the smart polymers display finely tunable recovery speed and exhibit greater than 92% shape fixing at −18°C or 0°C and full shape recovery at physiological temperature. Scanning electron microscopy analysis of fabricated scaffolds revealed a graded microporous structure, which mimics the nonuniform distribution of porosity found within natural tissues. With polycaprolactone serving as a control, human bone marrow-derived mesenchymal stem cell adhesion, proliferation, and differentiation greatly increased on our novel smart polymers. The current work will significantly advance the future design and development of novel and functional biomedical scaffolds with advanced 4D printing technology and highly biocompatible smart biomaterials.